Development of Argumentative Text Teaching Materials Using the Kialo Edu Application in Class XI of MAN 2 Deli Serdang - Tiarma Rokasih Sagala; Andini Ridwana; Mirna Putri Aulia; Sari Handayani Berutu; Trisnawati Hutagalung; Nurul Azizah (Raja Zulkarnain Education Foundation, 2026)
This study aims to develop argumentative text teaching materials based on the Kialo Edu application for grade XI students of MAN 2 Deli Serdang and analyze its feasibility and potential use in learning. The theoretical study emphasizes the importance of interactive and contextual digital teaching materials in accordance with the principles of the Independent Curriculum in improving students' critical thinking skills and argumentative literacy. The study used a qualitative approach with observation, interviews, literature studies, and documentation techniques. The results showed that Kialo Edu was able to facilitate the development of coherent arguments through visualization of the relationship between claims, supporting reasons, and rebuttals, thereby helping students understand argumentative logic more clearly. The developed teaching materials were declared appropriate based on the standards of material, content appropriateness, presentation, design, and graphics. In addition, the use of Kialo Edu increased student participation, the quality of argument revisions, collaborative skills, and courage in expressing opinions. Overall, Kialo Edu proved effective in supporting the learning of argumentative texts and was relevant to the demands of the Independent Curriculum which focuses on developing high-level reasoning skills.